Examining the acceptance of drone delivery services among Chinese consumers: A perspective from urban and rural areas - Jingqiong Wu; Ziwei Chen; Zhixian Zhang; Mingrui Cen (PLoS ONE, 2025)
Drones hold considerable promise in the realms of logistics and distribution, as they are expected to enhance the speed and efficiency of courier deliveries while simultaneously reducing associated costs. This study investigates Chinese consumers’ willingness to accept drone delivery services in the context of urban–rural disparities, conducting a comparative analysis to identify similarities and differences in the influencing factors across residential settings. The Technology Acceptance Model and the Environmental Literacy Model were extended incrementally using an approach to more comprehensively capture the factors influencing consumers’ willingness to adopt drone delivery services. Based on these extended frameworks, nine research hypotheses were proposed and empirically tested through a questionnaire survey. Data collected from 498 respondents was analyzed using a ridge regression model. Furthermore, using an additional independent test set of 102 questionnaires, we confirmed that ridge regression outperformed multiple linear regression in reducing error metrics, thereby demonstrating superior predictive accuracy and robustness. The results reveal significant regional differences in factors influencing consumers’ willingness to accept drone delivery services. In urban areas, environmental cognition, perceived usefulness, perceived ease of use and social norm significantly contribute positively to acceptance levels while perceived risk has a significant negative impact. Furthermore, policy support, UAV-environmental cognition, health safety, and service performance exert a relatively minor yet notable positive influence on acceptance levels within urban settings. In contrast, for rural consumers, environmental cognition, perceived usefulness, and perceived ease of use were key positive factors. UAV-environmental cognition and service performance also emerged as major contributors, exerting particularly strong positive effects on acceptance. Perceived risk negatively affected acceptance but to a lesser extent than in urban areas, whereas health safety, policy support, and social norm show no significant impact. Given these pronounced urban–rural disparities, logistics providers and policymakers are advised to implement context-specific, differentiated strategies: urban areas should focus on risk mitigation, regulatory enhancement, and policy incentives, whereas rural areas would benefit from increased awareness campaigns, pilot demonstrations, and infrastructure investment. Such targeted approaches are essential for optimizing the adoption and societal benefits of drone delivery services across diverse consumer groups.